One‐Pot Synthesis of Cyclodextrin‐Doped Cu‐SiO2 Catalysts for Efficient Hydrogenation of Dimethyl Oxalate to Ethylene Glycol. Issue 24 (29th November 2017) - Ye, Run‐Ping; Lin, Ling; Liu, Chang‐Qing; Chen, Chong‐Chong; Yao, Yuan‐Gen
Abstract: The β‐cyclodextrin (β‐CD) was successfully applied to synthesize Cu‐SiO2 catalysts by the sol‐gel method. The first and most important question addressed was increasing the copper loading with higher dispersion in the silica support. Another task was to elucidate the structure–performance relationship. Furthermore, catalysts with various β‐CD doping levels were systematically characterized and employed in the hydrogenation of dimethyl oxalate (DMO) to ethylene glycol (EG). The 0.1CD‐Cu‐SiO2 catalyst with 17.39 wt % copper showed 99.9 % DMO conversion and the highest EG selectivity of 95.0 % at 210 °C, as well a lifetime of over 240 h. The reaction results disclosed that the catalytic performance could be tuned facilely by changing the amount of β‐CD doping, which effectively influenced the Cu metallic surface area and dispersion. Abstract : Cyclodextrin doping : A series of cyclodextrin‐doped Cu‐SiO2 catalysts are prepared by a one‐pot synthesis method. The catalysts largely enhance the selectivity of the dimethyl oxalate to ethylene glycol hydrogenation and have long‐term durability.